The Influence of the Green Campus Program on Students' Environmentally Friendly Behavior - Putri, Neza Navilla; Vandan Wiliyanti; Yetri (Journal of Educational Management Research, 2025)
This study examines the impact of the green campus program at higher education institutions on students' environmentally friendly behavior and its contribution to sustainable development on campus and in surrounding communities. The green campus initiative addresses global environmental concerns by promoting responsible policies and behaviors. A quantitative approach was used, with data analysis conducted using Orange Data Mining software. The sample comprised 500 respondents from various study programs at the Faculty of Tarbiyah and Teacher Training, including environmental ambassador students at the State Islamic University of Raden Intan Lampung. Results showed positive perceptions of waste management facilities (mean = 4.04; SD = 0.9) and environmentally friendly transportation (mean = 3.68; SD = 1.03). However, pro-environmental behavior remained uneven, influenced by personal and institutional factors. The study recommends enhancing environmental education and support facilities to improve the program’s effectiveness. These findings offer strategic insights for other institutions implementing green campus initiatives.